Ecological crisis and the Church: A proposal for biblical stewardship as a nexus for environmental protection - Magezi, Christopher (Missionalia, 2025)
There is a growing global concern for environmental issues, and stakeholders, including governments, are trying to address the situation in various ways. Unfortunately, the Church, as an ordained community of God, seems to be refraining from engaging in such matters; thus, it remains on the periphery of related public discussions and debates, yet it has the potential to offer significant contributions. There is a dearth of theological research in this proposed area, and none of the few available studies has successfully developed theologies of mission to challenge the Church and, consequently, Christians to protect the environment, so as to mitigate climate change and environmental degradation. As a result, theology has little influence on public discourse pertaining to the prevailing environmental challenges. Given this, the aim of this paper is to propose biblical stewardship as a nexus for environmental protection. That is, the concept of stewardship can persuade the Church to be a significant stakeholder in the global efforts to protect the environment.